Teacher competency training in TEFA learning and scientific work at SMKN 4 Sukabumi - Agus Setiawan; Aam Hamdani; Mumu Komaro; Nisaudzakiah Utami; Nisa Aulia Saputra (Jurnal Abmas, 2025)
The training program to improve teacher competency in Teaching Factory (TEFA) and writing scientific papers is a strategic effort to encourage the improvement of the quality of education at SMKN 4 Sukabumi. This training was carried out because of a lack of understanding of vocational school teachers about implementing TEFA. This activity is designed to equip teachers with in-depth knowledge and practical skills to apply the TEFA concept based on the needs and work culture of the industry. The training is also focused on improving teachers' ability to write scientific papers as part of professional development and contributing to strengthening the academic literacy culture in schools by using training methods with an adult education approach. This training enabled teachers to develop applicable and contextual learning plans aligned with the evolving demands of the workforce. The results showed a significant improvement in understanding TEFA concepts and scientific writing skills. The impact is not only seen in the quality of the learning process, but also in the closer connection between schools and industry, as well as increasing teacher motivation to continue to innovate in daily teaching practices to create competent and work-ready graduates.   Abstrak Pelatihan peningkatan kompetensi guru dalam pembelajaran Teaching Factory (TEFA) dan penulisan karya ilmiah merupakan upaya strategis dalam mendorong peningkatan kualitas pendidikan di SMKN 4 Sukabumi. Pelatihan ini dilakukan dengan alasan masih rendahnya pemahaman guru SMK tentang penerapan TEFA di sekolah. Kegiatan ini dirancang untuk membekali para guru dengan pemahaman mendalam serta keterampilan praktis dalam menerapkan konsep TEFA yang berbasis pada kebutuhan dan budaya kerja industri. Pelatihan juga difokuskan pada peningkatan kemampuan guru dalam menulis karya ilmiah sebagai bagian dari pengembangan profesional dan kontribusi terhadap penguatan budaya literasi akademik di sekolah dengan menggunakan metode pelatihan dengan pendekatan pendidikan orang dewasa. Melalui pelatihan ini, guru diharapkan mampu menyusun rancangan pembelajaran yang aplikatif, kontekstual, serta selaras dengan tuntutan dunia kerja yang terus berkembang. Hasil yang diperoleh menunjukkan adanya peningkatan signifikan dalam pemahaman konsep TEFA dan kemampuan menulis ilmiah. Dampaknya tidak hanya terlihat pada kualitas proses pembelajaran, tetapi juga pada keterhubungan yang lebih erat antara sekolah dan dunia usaha/industri, serta meningkatnya motivasi guru untuk terus berinovasi dalam praktik mengajar sehari-hari demi menciptakan lulusan yang kompeten dan siap kerja. Kata Kunci: guru; karya tulis ilmiah; sekolah menegah kejuruan; teaching factory; TEFA